2016
DOI: 10.1088/0031-9155/61/14/5166
|View full text |Cite
|
Sign up to set email alerts
|

Impact of reconstruction parameters on quantitative I-131 SPECT

Abstract: Iodine-131 (131 I) has been used for diagnosis and therapy in Nuclear Medicine Centers in Brazil for more than 50 years. The present study aims to investigate the impact of the counts density and the reconstruction parameters in the calibration factor determination and in the image quantification, considering the reality of Brazilian dosimetry studies. For this task, images were quantified using calibration images with high and low counts density and reconstructed adopting two different parameters approaches, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…Similarly, the measurements of activity concentration in the background region of the Hotwater phantoms (table 6) further support our claim that, in the absence of PVE, the SPECT imaging provides quantitatively accurate activity estimation (errors <10% for ME and HE). The accuracy achieved in this study for 188 Re is similar to that reported by other phantom studies of 99m Tc, 111 In, 131 I (Shcherbinin et al 2008) and 177 Lu (Ljungberg et al 2015, Uribe et al 2017, demonstrating that the standard reconstruction with corrections yields relatively accurate quantification of 188 Re total activities. The remaining challenge, however, is image segmentation and partial volume effect corrections on nuclear medicine images.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Similarly, the measurements of activity concentration in the background region of the Hotwater phantoms (table 6) further support our claim that, in the absence of PVE, the SPECT imaging provides quantitatively accurate activity estimation (errors <10% for ME and HE). The accuracy achieved in this study for 188 Re is similar to that reported by other phantom studies of 99m Tc, 111 In, 131 I (Shcherbinin et al 2008) and 177 Lu (Ljungberg et al 2015, Uribe et al 2017, demonstrating that the standard reconstruction with corrections yields relatively accurate quantification of 188 Re total activities. The remaining challenge, however, is image segmentation and partial volume effect corrections on nuclear medicine images.…”
Section: Discussionsupporting
confidence: 87%
“…Different methods for camera calibration have been proposed (Dewaraja et al 2012, Ljungberg et al 2015. The point source planar method is a simple method and it is expected to provide accurate estimates of activity if all the image-degrading factors are properly compensated during the reconstruction (Uribe et al 2017). Alternatively, if the reconstruction algorithm is not fully quantitative, a CF derived from a tomographic acquisition of a large phantom filled with activity is recommended as it is expected that in this case both the calibration phantom and patient images would suffer from the same quantification inaccuracies (Dewaraja et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An overview of the most recently applied methods for SPECT/ CT quantification with therapeutically used radionuclides, different phantom geometries, volumes, camera vendors, reconstruction methods, and the related accuracies has been provided by Tran-Gia et al (24). Table 1 shows only publications with reported accuracies of less than 10% (25)(26)(27)(28)(29)(30)(31)(32).…”
Section: Image Quantificationmentioning
confidence: 99%
“…Therefore, patient imaging requires different set of reconstruction parameters for each acquisition [13]. The most widely used iterative reconstruction algorithm in clinical routine is the ordered subset expectation maximization (OSEM) scheme [11]. The iterative reconstruction allows the modeling of various effects, such as photon scatter and attenuation.…”
Section: Introductionmentioning
confidence: 99%